Inclusive search for standard model Higgs boson production in the WW decay channel using the CDF II detector. - Aaltonen, T; Adelman, J; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; et al. (2010)
We present a search for standard model (SM) Higgs boson production using pp collision data at square root(s) = 1.96 TeV, collected with the CDF II detector and corresponding to an integrated luminosity of 4.8 fb(-1). We search for Higgs bosons produced in all processes with a significant production rate and decaying to two W bosons. We find no evidence for SM Higgs boson production and place upper limits at the 95% confidence level on the SM production cross section (sigma(H)) for values of the Higgs boson mass (sigma(H)) in the range from 110 to 200 GeV. These limits are the most stringent for m(H) > 130 GeV and are 1.29 above the predicted value of sigma(H) for c = 165 GeV.